Palladium nanoparticles supported on manganese oxide–CNT composites for solvent-free aerobic oxidation of alcohols : tuning the properties of Pd active sites using MnOx - Tan, Huiteng (2013)
The manganese oxide-multi-walled carbon nanotube (MnOx/CNT) composite was successfully synthesized following a surface deposition method. Subsequently, the palladium nanoparticles were homogeneously deposited onto this MnOx/CNT hybrid material followed by being reduced under H2 atmosphere. The catalytic activity in solvent-free benzyl alcohol oxidation was correlated with MnOx loading, indicating the important role of manganese oxide in tuning the properties of Pd catalytic active site, e.g., dispersion and electron density. In the presence of reducible MnOx on CNT, the electron transfer and oxygen activation were greatly enhanced because of the synergistic interaction between Pd metallic nanoparticles and the hybrid support materials. Due to this strong metal support interaction (SMSI), the Pd/MnOx/CNT catalysts were remarkably stable against deactivation.